ACCOUNTING INFORMATION TECHNOLOGY AND PERFORMANCE OF LISTED OIL AND GAS COMPANIES IN NIGERIA - Cynthia , Edwin-Njoku Chizoba (International Journal of Accounting & Finance Review, 2025)
The oil and gas industry is the primary generator of government revenue in Nigeria. Still, its extensive activities cause significant environmental damage, leading to widespread environmental devastation and hostile relations with host populations. The key gap in the current regulatory framework notwithstanding, there remains a gaping hole in the stringent accounting and reporting for green accounting, i.e., the systematic accounting of environmental costs and liabilities, in traditional financial reporting. This murkiness creates a risky environment for companies’ survival in unstable places like the Niger Delta. This paper examines the relationship between green accounting measures and the financial performance of oil and gas companies listed on the Nigerian stock exchange. The emphasis is on the effects of community development, rehabilitation, and charitable expenditures on net assets and net profit margins. The panel data method was used, and secondary data were collected from 10 listed oil and gas companies for the years 2004-2020, sourced from the Nigerian Stock Exchange Factbook and the companies’ annual reports. It was estimated using a fixed-effects model, which was verified by the Hausman test. The analytical toolkit included F-tests, t-tests, and coefficients of determination at the 5 percent significance level. According to the results, the explanatory variables predict 73.8 percent of the variation in net assets (F = 87.33, p = 0.05) and 15.6 percent of the variation in net profit margins (F = 1.16, p = 0.327). The regression analysis indicates that net assets are negatively associated with both community development and rehabilitation costs. Still, donations and charitable contributions have a significant positive impact on net assets (coefficient = 0.399). The results indicate that green accounting practices have a substantial effect on firm wealth, in terms of net assets, but have only a minor impact on profitability, in terms of the net profit margin. Environmental and social cost burdens will decrease asset value in the short run, whereas strategically implemented charitable donations will increase corporate status. The paper proposes formal encouragement of green accounting policy measures to achieve long-term sustainability and transparency in the industry. JEL Classification Codes: M41, Q56, L71, M14, G32.